Exercise training protects human and rodent β cells against endoplasmic reticulum stress and apoptosis. Issue 3 (3rd January 2018) - Paula, Flavia M. M.; Leite, Nayara C.; Borck, Patricia C.; Freitas‐Dias, Ricardo; Cnop, Miriam; Chacon‐Mikahil, Mara P. T.; Cavaglieri, Claudia R.; Marchetti, Piero; Boschero, Antonio C.; Zoppi, Claudio C.; Eizirik, Decio L.
Abstract : Prolonged exercise has positive metabolic effects in obese or diabetic individuals. These effects are usually ascribed to improvements in insulin sensitivity. We evaluated whether exercise also generates circulating signals that protect human and rodent β cells against endoplasmic reticulum (ER) stress and apoptosis. For this purpose, we obtained serum from humans or mice before and after an 8 wk training period. Exposure of human islets or mouse or rat β cells to human or rodent sera, respectively, obtained from trained individuals reduced cytokine (IL‐1β+IFN‐γ)‐ or chemical ER stressor‐induced β‐cell ER stress and apoptosis, at least in part via activation of the transcription factor STAT3. These findings indicate that exercise training improves human and rodent β‐cell survival under diabetogenic conditions and support lifestyle interventions as a protective approach for both type 1 and 2 diabetes.—Paula, F. M. M., Leite, N. C., Borck, P. C., Freitas‐Dias, R., Cnop, M., Chacon‐Mikahil, M. P. T., Cavaglieri, C. R., Marchetti, P., Boschero, A. C., Zoppi, C. C., Eizirik, D. L. Exercise training protects human and rodent β cells against endoplasmic reticulum stress and apoptosis. FASEB J. 32, 1524–1536 (2018). www.fasebj.org